Edukasi Kesehatan Tentang Pengaruh Pemakaian Diapers Yang Menyebabkan Ruam Popok (Diaper Rash) Terhadap Ibu Di Klinik EvieTahun 2022 - Ade Rachmat Yudiyanto; Damayanty S; Ingka Kristina Pangaribuan (Universitas Maritim AMNI Semarang, 2022)
Diaper rash is a complaint of red spots on the genitals and buttocks of babies wearing diapers caused by skin rubbing against diapers (Dwi Maryanti, et al, 2011). Diaper rash often occurs in the area around a baby's buttocks due to the use of diapers that are rarely changed, are too tight, or are used for too long. Usually the rash is not dangerous, but it can cause pain and cause anxiety in the baby and parents. According to a report by the Journal of Pediatrics, there were 54% of babies aged 1 month who experienced diaper rash after using